PERAN SISTEM INFORMASI PEMASARAN DALAM MENINGKATKAN LOYALITAS PELANGGAN PADA TOKO ONLINE - Nasution, Tri Rahmadani; Padli Nasution, Muhammad Irwan (Jurnal Ilmiah Sistem Informasi, 2024)
The development of information technology has changed the way people shop from traditional methods to electronic trading systems or E-Commerce. This change is further driven by the COVID-19 pandemic, which makes people turn to online shopping for their daily needs. This study aims to evaluate the role of marketing information systems in supporting customer loyalty on e-commerce platforms. The research uses the literature review method to analyze various literatures related to E-Commerce, marketing information systems, customer loyalty, and content personalization. The results show that marketing information systems play an important role in content personalization, product recommendations, and loyalty programs, which increase customer engagement and loyalty. The system also enables more responsive decision-making and improves operational efficiency. Effective implementation of marketing information systems can provide a more personalized and relevant experience for consumers, thereby increasing customer satisfaction and brand loyalty.